Ziehl Neelsen vs. Auramine staining technique for detection of acid fast bacilli - Gurung, Rajendra; Shrestha, R; Poudyal, N; Bhattacharya, SK (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: The culture and molecular test are the best methods for isolation and identification of Mycobacterium tuberculosis in developed countries. But, in developing countries like Nepal with a significant number of tuberculosis (TB) cases and limited resources, the diagnosis of TB relies primarily on smear microscopy for Acid fast bacilli (AFB). Objective: To compare the results of direct sputum examination for AFB stained by Ziehl Neelsen and Auramine technique. Method: Cross sectional comparative study was conducted in tuberculosis research laboratory, BPKIHS from April to June 2013. A total of 100 sputum samples were collected randomly. Four slides were smeared and labeled for each as neat ZN, neat Auramine, concentrate ZN and concentrate Auramine. Slides were processed as per WHO laboratory guidelines. Results: The findings of this study revealed that 3% positive with neat Auramine was negative for ZN stain. Similarly, 5% positive cases with Auramine concentrate were negative with ZN concentrate technique. Auramine stain was able to detect all ZN positive as positive but only 83 cases were detected as negative among 88 case of ZN negative. Both concentration techniques showed 12% of positive with significant relationship. With this; Auramine showed 100% sensitivity, 94.6% specificity, positive predictive values and negative predictive values 70.5, 100% respectively. Conclusion: Auramine stain stands efficient on comparison and can be used as an alternative to ZN stain, with added value of allowing a large number of sputum specimens to be examined in a given time as low power is used for examination. Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, Page: 59-66